Aircraft Accident and Injury Prevention in Namibia - Amweelo, Moses (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
An accident is an unexpected, unplanned and unwanted event that disrupts work and may result in human injury or death, damage to property, loss of production, time and money. It follows therefore that occupational ergonomics must be developed and improved to prevent accidents and injuries. This is done by removing hazards, reducing the probability of accidents and minimizing the severity of accident consequences. This is an abstract of a study paper that takes the above into consideration, regarding aircraft accidents and injuries in Namibia. Aviation has traditionally been one of the most important transport sectors in the Namibian economy. This is primarily because the country consists of vast but breathtakingly beautiful wilderness and deserts that are sparsely inhabited and more easily accessible by air than by road. With over 500 civil registered aircraft, over 930 pilots, and over 70 aircraft operators frequently servicing the tourism, business postal, mining, farming and other sectors it is not difficult to see that aircraft accident and injury prevention is a major concern in the country. A systematic approach toward identification, categorisation and remedy of aircraft accidents and incidents has therefore been developed in Namibia that conforms to internationally accepted standards and practices. This has been done by giving due consideration to the level of training given to aviation personnel, the type of aircraft operated in Namibia and the unique environment in which aviation activities are carried out within the country. The purpose of this study was to assess the occupational ergonomics of aircraft accident and injury prevention in Namibia with particular regard to the following areas:? A detailed analysis on the number of aircraft accidents and incident (occurrences) taking place in Namibia and their socio-economic consequences.? A statistical research of these occurrences vis-à-vis the size of the aviation industry in Namibia.m? A classification of these occurrences by type in technical and ergonomic terms. ? A provision of the hazard and risk assessment process (by means of an example) to prevent further occurrences taking place in Namibia